Analisis Keberpihakan Presiden dalam Kampanye Politik Berdasarkan Pasal 281 Undang-Undang No 7 Tahun 2017 tentang Pemilu - Indra Purwanto; Ali Maskur (Universitas Semarang, 2025)
This research aims to analyze the President's partisanship in political campaigns based on Article 281 of Law Number 7/2017 on General Elections. This issue is important because it concerns the integrity of democracy and public trust in the institution of the presidency. The urgency of this study increased after the President of the Republic of Indonesia showed a symbolic gesture of support for one of the candidate pairs and conveyed his intention to “cawe-cawe” in organizing the 2024 Election. This research uses an empirical juridical method with a literature study approach to legislation, legal literature, and content analysis of print and electronic media coverage. The novelty of this research lies in the focus of analysis on the ambiguity of Article 281 norms that have not specifically regulated the role of the president as a political actor as well as head of state in the context of the campaign. The results show that the President's actions have the potential to violate the principle of neutrality as stipulated in Article 281. On the other hand, the norm is considered multi-interpretive and potentially contradicts Article 4 of the 1945 Constitution, which places the President as the holder of government power. This study concludes that Article 281 of Law No. 7/2017 needs to be revised because it has the potential for multiple interpretations of the President's position in the constitutional system, and risks blurring the line between political authority and ethics of state office. Penelitian ini bertujuan untuk menganalisis keberpihakan Presiden dalam kampanye politik berdasarkan Pasal 281 Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum. Isu ini penting karena menyangkut integritas demokrasi dan kepercayaan publik terhadap institusi kepresidenan. Urgensi kajian ini meningkat setelah Presiden Republik Indonesia menunjukkan gestur simbol dukungan kepada salah satu pasangan calon serta menyampaikan niat untuk “cawe-cawe” dalam penyelenggaraan Pemilu 2024. Penelitian ini menggunakan metode yuridis empiris dengan pendekatan studi literatur terhadap peraturan perundang-undangan, literatur hukum, serta analisis konten dari pemberitaan media cetak dan elektronik. Kebaruan penelitian ini terletak pada fokus analisis terhadap ambiguitas norma Pasal 281 yang belum secara spesifik mengatur peran presiden sebagai aktor politik sekaligus kepala negara dalam konteks kampanye. Hasil penelitian menunjukkan bahwa tindakan Presiden berpotensi melanggar prinsip netralitas sebagaimana diatur dalam Pasal 281. Di sisi lain, norma tersebut dinilai multitafsir dan berpotensi bertentangan dengan Pasal 4 UUD 1945 yang menempatkan Presiden sebagai pemegang kekuasaan pemerintahan. Penelitian ini menyimpulkan bahwa Pasal 281 UU No. 7 Tahun 2017 perlu direvisi karena berpotensi multitafsir terhadap posisi Presiden dalam sistem ketatanegaraan, serta berisiko mengaburkan batas antara kewenangan politik dan etika jabatan kenegaraan.